Results of 5-year monitoring of the circulation of seasonal Сoronaviruses in hospitalized children in the pre-pandemic period - V. N. Timchenko; V. F. Sukhovetskaya; T. M. Chernova; T. A. Kaplina; M. D. Subbotina; O. V. Bulina; М. М. Pisareva (Детские инфекции (Москва))
Coronaviruses can cause damage to various parts of the respiratory system, gastrointestinal tract, and other organs and systems.The aim of the study: to monitor the circulation of seasonal coronaviruses in hospitalized children in the pre-pandemic period.Materials and methods: real-time multiplex PCR was used to test samples of nasopharyngeal mucus from 2188 patients aged 1 monthto 17 years, hospitalized with acute respiratory infection in 2014—2018. The results are presented with the indication of the fractions (%) and the calculation of the 95% confidence interval according to Klopper-Pearson. The differences between the groups were evaluated using the Pearson χ2 test. The differences in the groups were considered statistically significant at the level of the criterion p< 0.05.Results: monitoring of the circulation of pathogens of acute respiratory viral infection (ARVI) during 5 epidemic seasons showed that the appearance of a new subtype of coronavirus in 2019 was preceded by a gradual displacement of influenza, RS-and bocavirus infections from the circulation due to a statistically significant increase in the proportion of seasonal coronaviruses from 3.6% in 2014—2015 to 10.8% in the prepandemic season 2018—2019 (p= 0.007). The circulation of seasonal coronaviruses had a distinct seasonality (november-april)with the peak of registration in february (28.4%) and march (36.7%). Seasonal coronaviruses were detected in 7.3% of hospitalized children with ARVI, with a predominance in the age groups under 2 years (58.2%) and 3—6 years (25.4%). Hospitalization was more often required for patients with lower respiratory tract lesions (58.2%), a fifth of which was pneumonia (21.8%). In most children, ARVI caused by coronaviruses occurred as a monoinfection (79.9%), combined infection with other pathogens was observed in 20.1% of cases with fluctuations from 18.2% to 28.6% in different epidemic seasons. Viral associations are most common in young children (85.2%).